PENGARUH LATIHAN PASSING TRIANGLE PASIF DAN AKTIF TERHADAP ACCURACY PASSING DALAM PERMAINAN FUTSAL ANAK SEKOLAH DASAR - Soemantri, Rizky; Sudrazat, Adang; Rukmana, Anin (JURNAL ILMU KEOLAHRAGAAN, 2024)
Futsal is a sport played by 2 teams of 5 people and is a popular sport. Basic futsal techniques include passing, control, dribbling, shooting and heading. The experimental method was used by the researcher in this study. The research design used quasi-experimental "Two group pretest-posttest design". The instrument in this study was to use a short passing test from the results of the Independet t-test which obtained a tcount value of 4,544 and ttable 2,306. For decision making, i.e. comparing them, it can be seen that 4,544 > 2,306. The alternative hypothesis (Ha) which reads "there is a significant influence of passive and active passing triangle training on the passing accuracy of SDN 3 Wangunsari students" is accepted., so this study proves the research hypothesis and concludes that there is an effect of Passive Passing Triangle and Active Passing Triangle exercises on increasing passing accuracy in Wangunsari Elementary School students with a calculation value of 4,544 and a table of 2,306